Minority Ethnic, Race and Sect Relations in Pakistan:Hazara Residing in Quetta - Sarfraz Khan Professor, Area Study Center, University of Peshawar Noor Ul Amin Islamia College Univeristy, Peshawar (The Journal of Humanities & Social Sciences, 2019)
This paper charts systematic persecution, ethnic profiling, target killing, kidnapping, harassment, racial discrimination and ghettoization, ethnic Hazara face in Quetta.The Hazara, a marginalized ethnicity severely discriminated, began migrating initially into British India, from Afghanistan, in 1890s. During 1962- 63, the government of Pakistan granted ethnic Hazara citizenship rights. Constitutionally, they were to enjoy equal rights, might form political parties, to represent them in elected bodies of Balochistan and Pakistan. Previously, ethnic Hazara individuals rose to the positions of:Generals; rather, Chief of the Army Staff; and to Federal/ProvincialMinisters/Governors, in Pakistan. However, the Hazara began facing discrimination and ethnic, cultural as well as confessional (a majority of Hazara profess Shia sect of Islam) persecution, in Pakitan, in the last two deacades of the previous mellenium, at unofficial, and continue to face, both, at official and unofficial levels. Since 2012, computerised National Identity Cards of ethnic Hazara in Quetta have been suspended/blocked, a step tentamount to denial of citizenship rights of Pakistan. A Sunni militant terrorist outfit, Lashkar-Jhangive, warned ethnic Hazara of turning Pakistan into their graveyard, in case, they did not leave this country. Following the Iranian revolution ensuing Iran/Saudi (Shia- Sunni) the conflict resulted in a proxy war. Hazara leaders suspect, systematic persecution of Hazara, aims at, evicting them of expensive land they occupy in and around Quetta. They view ethnic profiling/cleansing not only as attempts to force Hazara to sell their houses and businesses at throw-away prices, suspecting their loyalties, and reversing 1962-63 official notification, that recognizes the ethnic Hazara Pakistani citizens.